Localizing SDG in Eastern Region Malaysia: Key Challenges of Project Impact Evaluation - Puteh, Fadilah; Wan Abdul Halim, Wan Puspa Melati (Journal of Technical Education and Training, 2023)
The Solution Provider Project for the community throughout Peninsular Malaysia, Sabah, and Sarawak is one of the remarkable flagship programs of The All-Party Parliamentary Group Malaysia – Sustainable Development Goals by Civil Society Organization Alliance (APPGM-SDG CSO). With the clear aim to promote Sustainable Development Goals (SDGs) in Malaysia, several projects for 2022 have been implemented throughout the country including 10 solution projects in the Eastern Region, particularly in Kelantan. The solution project implementors were given financial assistance to run skill-based training and community-based projects for community development, empowerment, and an industry-ready talent pool. This paper intends to discuss the key challenges and project impact evaluation carried out on behalf of APPGM-SDG. The methodology employed was a mixed method – embedded design approach to assess the project impact evaluation. Both qualitative and quantitative approaches were used to evaluate the impact of the project. Data was gathered from proposal and project monitoring documents, focus group discussions (FGD), and site visits. Findings from solution providers, project beneficiaries, and evaluators' observations were then combined and triangulated to provide a more in-depth understanding of the impact of the solution projects. There were several key challenges found in the solutions projects from the perspectives of solution providers, project beneficiaries, and project evaluators in the Eastern region discussed in this paper. This paper also highlights several recommendations to overcome those challenges via a clear communication plan between solution providers, APPGM representatives, and impact evaluators to facilitate and strengthen the impact evaluation process. The challenges discussed in this paper are hoped to better inform project implementors and policymakers in their decision-making, program design, and policy papers, particularly in the areas of economic, social, and environmental with a clear target SDG deliverables and target group.